Postharvest freezing process assessment of the blueberry structure in three acts: Bioimpedance, color, and granulometry analysis. (November 2021) - Arteaga, Hubert; Robleto-Martinez, Eduardo; Carolina de Sousa Silva, Ana; Souto, Sergio; Batista, Jacimaria; Xavier Costa, Ernane José
Abstract: The bioelectrical impedance, cell granulometry and the color of the freeze-thawed blueberries were investigated. The blueberries were subjected to freezing at −18 °C for 135 min, during this process, groups were removed to every 9 min, and stored at 4 °C until further analysis. Bioelectrical impedance, color, pH, total soluble solids and cell granulometry were measured. The characteristics of bioelectrical impedance, cell granulometry and color were analyzed by computational algorithms, which allowed extracting characteristic of blueberries during the freezing process. The results showed progressive loss of the cellular structure during freezing, this behavior was associated with the bioimpedance parameters. The cells damage also influenced color parameters, and cell granulometry. The color followed the direction toward darkness and more intense red-blue tones, which suggest the migration of pigments from the blueberry's skin towards the flesh. In conclusion, evaluation of the color and cell granulometry by computational algorithms with bioelectrical impedance provides a powerful tool for evaluating cell damage in blueberries during the freezing process. Highlights: Track the blueberry structure during the freezing process by computational methods. Details of impedance and image processing to evaluate blueberry-freezing process. Provide a low cost way to evaluate fruit freezing. Bioelectrical impedance is able to monitor postharvest fruit freezing process. Combining three technologies to evaluate cell damage in fruits during freezing.